Development of stability indicating HPTLC method for estimation of antihypertensive drug combination nifedipine and valsartan. Issue 1 (11th December 2019) - Shah, Dimal A.; Patel, Jaimin S.; Jadeja, Priyanka; Patel, Vandana B.; Chhalotiya, Usmangani K.
ABSTRACT: A precise and accurate method for the analysis of antihypertensive drug combination nifedipine and valsartan was developed using the HPTLC method. The stationary phase used was a pre-coated silica gel G60 – F254 aluminium sheet and the mobile phase was acetonitrile: methanol: n -butanol: acetic acid (6:2:2:0.1, v/v/v/v). The detection of spots was carried out densitometrically using a UV detector at 230 nm in the absorbance mode. The Rf values of valsartan and nifedipine were found to be 0.25 and 0.65, respectively. The calibration curve was found to be linear in the range of 120–320 ng/band and 900–2400 ng/band for nifedipine and valsartan, respectively. Forced degradation studies were performed using stress conditions like acid and base hydrolysis, photolytic, thermal and oxidative stress degradation to develop the stability indicating method. The degradation study indicated that nifedipine was susceptible to acid-base hydrolysis, oxidative stress degradation and photolytic degradation, while valsartan was susceptible to acid-base hydrolysis and oxidative stress degradation.